Rotational Speed Variation Governs Impact Strength in HDPE Friction Stir Welding: Variasai Kecepatan Rotasi Mempengaruhi Kekuatan Dampak pada Pengelasan Gesekan Putar HDPE - Firmansyah, Mohammad Hanif; Iswanto (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Friction Stir Welding is increasingly applied in polymer joining due to its solid-state mechanism and ability to produce stable joints without melting. Specific Background: High-Density Polyethylene requires appropriate process parameters to obtain optimal mechanical performance, particularly under impact loading. Knowledge Gap: Previous studies have discussed process parameters in metal and polymer welding, yet limited studies specifically address the relationship between rotational speed variation and impact strength characteristics in HDPE joints. Aims: This study aims to analyze the effect of spindle rotational speed variation on the impact strength and microstructural characteristics of HDPE joints produced by Friction Stir Welding. Results: The experimental findings demonstrate that rotational speed variation significantly alters impact strength values and joint morphology, where certain rotational settings generate more homogeneous structures and higher resistance to impact loading. Novelty: The study provides a focused experimental evaluation of rotational speed parameters on HDPE joints using impact testing and metallographic observation within a controlled setup. Implications: These findings contribute to parameter optimization strategies in polymer-based Friction Stir Welding and provide practical guidance for improving joint reliability in engineering applications. Keywords: Friction Stir Welding, High-Density Polyethylene, Rotational Speed, Impact Strength, Microstructure Key Findings Highlights Rotational parameter selection determines joint toughness performance. Homogeneous internal morphology correlates with higher absorbed energy values. Controlled spindle settings produce more stable polymer joint characteristics.